The impact of sustainable reporting on financial performance of companies - Vukovic, Bojana; Peštović, Kristina; Jakšić, Dejan (Industrija, 2025)
Environmental, social and corporate governance reporting (ESG) or sustainable reporting can impact a company's performance through financial outcomes, risk management, and long-term sustainability. This paper aims to determine the relationship between sustainable reporting and the financial performance of companies. The sample consists of 60 large Serbian companies who are required according to law to report non-financial information in the field of sustainability. The observed time frame is from 2021 to 2023. The empirical section concentrates on utilizing the non-parametric Mann-Whitney U test in SPSS. The results showed that there is a statistically significant difference in the financial performance between companies that have separate sustainability reports published on Serbian and those that do not. However, there is no statistically significant difference in the financial performance between companies that include the sustainability report within their annual business report and those that do not. The results will indicate the need to improve an organization's commitment to sustainable development in order to achieve better financial performance that leads to long-term survival, growth, and development.
Keywords: Sustainable reporting, Financial performance, Large companies, Serbia